A Correlation and Regression Approach to Phenology - Harper, Geoffrey (Sibbaldia: the International Journal of Botanic Garden Horticulture, 2009)
In this paper the developmental stages leading up to flowering are reviewed. It is then shown how correlation and regression methods of analysis can be used to identify the influence of air temperature at different developmental stages, using snowdrop and clover as case studies. Hypotheses are proposed to account for the findings, and it is suggested how such hypotheses could be tested. The implications for the construction of a functional phenological classification of plants are discussed.